Bizone: complete influencer marketing solution, low risk, high results - Al Maliki, Hanif Abd. Ar-rahman; Dzaky, Muhammad; Wulandari, Rifana; Rasipu, Muhammad Nur Alim; Anindya, Khoirina Noor; Sukardi, . (2025)
BizOne is a digital platform that connects businesses from Micro, Small, and Medium Enterprises (MSMEs) with influencers to optimise their marketing strategies. The platform addresses major challenges faced by businesses in selecting the right influencers and measuring the effectiveness of their collaborations. Performance-based payment is one of BizOne's key advantages, where businesses only pay influencers based on measurable results, such as engagement and awareness. This approach can increase brand visibility while saving costs, as payments are tied directly to outcomes, thus driving optimal sales and business growth. In addition, the platform is equipped with an analytics dashboard that allows businesses to monitor influencer performance in a transparent and data-driven manner. Not only that, BizOne also provides gamification-based interactive educational features that help users understand digital marketing strategies more effectively. With the combination of these excellent features, we present a solution that is more secure, efficient, and performance-based compared to similar platforms. The platform not only benefits businesses but also has a positive impact on influencers. With the system, well-performing influencers can build a credible and proven professional reputation through transparent data BizOne aims to foster a more transparent and trusted digital marketing ecosystem, helping businesses get a higher return on investment (ROI) and ensuring that every marketing investment provides maximum impact for both businesses and influencers who want to grow professionally.